White bagging, brown bagging and site of service policies: best practices in addressing provider markup in the commercial insurance market - Caroline Pearson; Lindsey Schapiro; Steven D Pearson (Becaris Publishing Limited, 2023)
New Institute for Clinical and Economic Review (ICER) analysis evaluates potential risks and advantages of reforms to current policies related to white bagging, brown bagging, and site of service policies that aim to address provider markup in the commercial insurance market.